If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(y + 3) + 3 = 19 Reorder the terms: 4(3 + y) + 3 = 19 (3 * 4 + y * 4) + 3 = 19 (12 + 4y) + 3 = 19 Reorder the terms: 12 + 3 + 4y = 19 Combine like terms: 12 + 3 = 15 15 + 4y = 19 Solving 15 + 4y = 19 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-15' to each side of the equation. 15 + -15 + 4y = 19 + -15 Combine like terms: 15 + -15 = 0 0 + 4y = 19 + -15 4y = 19 + -15 Combine like terms: 19 + -15 = 4 4y = 4 Divide each side by '4'. y = 1 Simplifying y = 1
| -26=-5w+3(w-4) | | 4n+6=n-6 | | 450w=510w-300 | | 4u+28=8(u+6) | | x/y=6/2 | | 6+2x=12-8x | | -9(v+6)=-6v-24 | | 40x+75=40x+35 | | 15x-7=2x-79 | | 7.5x+0.5x=68.40 | | .3x=.1x+2.9 | | -4w-46=2(w+4) | | 40x+35=40x+35 | | Z+9=84 | | 60=-15n | | X/5=3x-4/10 | | x^7=78 | | 55/x=11/5 | | 5u(-7u^3)= | | 8+2x+2=3x+5 | | 2f+3=7f-24 | | 4x+2(3x-9)=66 | | 11=1/4m-3m | | 7k^2-4k-20=0 | | -1p-5(1p+4)=-25-7p | | (2x=5)/3=y | | 9+4x=-63 | | 2y-12=y-5 | | 110/12 | | 4x^(3/2)=32 | | 14k/9=4k-198 | | 1/7*9/13 |